Integrated Content Marketing Strategy on Customer Journey to Build Brand Awareness of Jember Batik MSMEs in the Digital Era - Ahmad Izzuddin; Yohanes Gunawan Wibowo; Vesa Karsi Sukmawati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the implementation of integrated content marketing strategies at each stage of the customer journey, from awareness, consideration, decision, to retention and advocacy, and to evaluate their impact on increasing brand awareness.Methodology: The research method used is a qualitative case study approach, involving in-depth analysis of digital marketing practices, content observation, and documentation of promotional activities carried out by Jember's batik MSMEs.Results: The results show that implementing a structured, consistent, and integrated strategy across communication channels can increase brand visibility, strengthen positive associations, and create a seamless customer experience that encourages long-term loyalty.Applications/Originality/Value: This study confirms that customer journey-based content marketing is not just a promotional innovation, but a strategic necessity to ensure the sustainability and competitiveness of batik MSMEs in the digital era